ANALISIS YURIDIS PERJANJIAN PERKAWINAN BERDASARKAN UU NO.16 TAHUN 2019 TENTANG PERUBAHAN ATAS UU NO.1 TAHUN 1974 TENTANG PERKAWINAN DAN PUTUSAN MK NO.69/PUU-XIII/2015 - Lina Alfiana (Fakultas Hukum Universitas Islam Malang, 2021)
This study aims to understand and find out the marriage agreement in the Marriage Law and the Constitutional Court Decision No. 69 / PUU-XIII / 2015. Marriage agreements are rarely found in Indonesian society. The reason is because of the community's lack of understanding regarding the marriage agreement. The community considers that the marriage agreement is not important even though the Marriage Law has regulated it. Due to the community's lack of understanding regarding the marriage agreement, if the marriage takes place it will experience difficulties. In the Constitutional Court decision that was reviewed, there was no marriage agreement in mixed marriages (Indonesian and foreigners) which resulted in the loss of the applicant's rights which collided with the Marriage Law. The formulation of the problem is how the relevance of the Marriage Law and the Constitutional Court Decision No. 69 / PUU-XIII / 2015 on marriage agreements and how the legal consequences No. 69 / PUU-XIII / 2015. The research method used is a normative juridical research with a statutory and conceptual approach. The relevance of the Marriage Law and the Constitutional Court Decision on the marriage agreement is that both discuss marriage agreements, are interrelated and complementary. Meanwhile, the legal consequences of the Marriage Law and the Constitutional Court Decision on marriage agreements are legal certainty, are binding, retroactive, binding third parties, and marriage agreements can be changed / renewed during the marriage period.Penelitian ini bertujuan untuk memahami dan mengetahui perjanjian perkawinan dalam Undang-undang Perkawinan dan Putusan MK No. 69/PUU-XIII/2015. Perjanjian perkawinan masih jarang ditemui di masyarakat Indonesia. Penyebabnya adalah karena ketidakpahaman masyarakat terkait perjanjian perkawinan. Masyarakat menganggap bahwa perjanjian perkawinan bukanlah suatu yang penting meskipun Undang-Undang Perkawinan telah mengaturnya. Karena ketidak pahaman masyarakat terkait perjanjian perkawinan, maka apabila berlangsungnya perkawinan maka akan mengalami kesulitan. Dalam putusan MK yang dikaji yaitu tidak adanya perjanjian perkawinan dalam perkawinan campuran (WNI dan WNA) yang mengakibatkan hilangnya hak-hak pemohon yang terbentur dengan Undang-Undang Perkawinan. Rumusan masalah yaitu bagaimana relevansi UU perkawinan dan putusan MK No. 69/PUU-XIII/2015 terhadap perjanjian perkawinan dan Bagaimana akibat hukum No. 69/PUU-XIII/2015. Metode penelitian yang digunakan menggunakan jenis penelitian yuridis normatif dengan pendekatan undang-undang dan konseptual. Relevansi antara UU Perkawinan dan Putusan MK terhadap perjanjian perkawinan adalah sama-sama membahas perjanjian perkawinan, saling berkaitan, dan saling melengkapi. Sedangkan akibat hukum UU Perkawinan dan Putusan MK terhadap perjanjian perkawinan yaitu adanya kepastian hukum, bersifat mengikat, berlaku surut, mengikat pihak ketiga, dan perjanjian perkawinan dapat dirubah/diperbarui selama masa perkawinan.